Reflections on using community-based action research with a group of women/youth to explore the socio-emotional factors that enhance or inhibit participation in sustainable poverty alleviation initiatives - Petersen, Melanie (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEdPsych)--Stellenbosch University, 2020.